EKSPLORASI GUNUNG ES DAN PROSES “U” SEBAGAI SEBUAH METODE PEMBELAJARAN DALAM PELATIHAN PENGUATAN MODERASI BERAGAMA - Fauzan, Mohamad; Restendi, Dedi (JENTRE, 2024)
This study aims to assess the effectiveness of the Iceberg Analysis and U-Process methods in training programs designed to strengthen religious moderation, using the Kirkpatrick model to evaluate reaction and learning levels. A survey and descriptive analysis were employed to measure training effectiveness. The study involved a population of 90 participants, with a sample size of 73 determined using the Morgan and Krejcie sample formula. The instrument's validity and reliability were tested, and a Paired Sample T-Test was used to analyze learning outcomes. Descriptive analysis was conducted based on the Iceberg Analysis and U-Process learning models. The findings indicate that the training evaluation at the reaction level falls into the "very good" quadrant, with all aspects of the organizers and instructors rated positively. Learning outcomes show a significant improvement, and at the results level, the learning processes involving the Iceberg and U-Process methods significantly enhanced participants' knowledge and skills. Overall, the training is deemed effective.